Fiscal Response to a Temporary Trade Shock: The Aftermath of the Kenyan Coffee Boom. - Bevan, D; Collier, P; Gunning, J (1989)
The appropriate fiscal response to a temporary terms of trade windfall is difficult to determine, even in an unregulated economy. But controls, such as those in force during the 1976- 79 coffee boom in Kenya, introduce special problems. For example, foreign exchange controls make the private investment of boom income inefficient by causing it to be undertaken too rapidly. In Kenya the boom induced a massive increase in public expenditure, far in excess of the increase in public revenue. The net effect on capital formation was negative because the fiscal response exacerbated the rise in the relative price of nontraded capital goods, and because resources were preempted for government consumption.